2019
DOI: 10.1111/1365-2664.13408
|View full text |Cite
|
Sign up to set email alerts
|

Remotely sensed primary productivity shows that domestic and native herbivores combined are overgrazing Patagonia

Abstract: 1. Carrying capacity is the maximum animal density an area can sustain without deterioration of its resources. Overgrazing has degraded Patagonia, but sheep stocks decreased and gave way to mixed systems with cattle, goats and guanacos (native wild camelids).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…The main argument of Marino et al (2020) is that grazing is not at equilibrium because domestic stocks have been withdrawn or lost in large areas of Patagonia, with the remaining animals concentrated and overgrazing still-productive land. We agree with this view, but we consider that it does not contradict our previous conclusions because the historic trend of domestic stocks to adjust to carrying capacity at a regional (and even provincial) scale in the last century shown by hard data in Oliva et al (2019) does not preclude the existence of overgrazing and under-grazing at smaller (local) scales. Marino et al (2020) estimated that land that remains dedicated to sheep production would have 73% and 28% overgrazing in Santa Cruz and Chubut Provinces, respectively.…”
Section: Are Dome S Ti C S To Ck N Umb Er S At Equ Ilib Ri Um With supporting
confidence: 84%
See 3 more Smart Citations
“…The main argument of Marino et al (2020) is that grazing is not at equilibrium because domestic stocks have been withdrawn or lost in large areas of Patagonia, with the remaining animals concentrated and overgrazing still-productive land. We agree with this view, but we consider that it does not contradict our previous conclusions because the historic trend of domestic stocks to adjust to carrying capacity at a regional (and even provincial) scale in the last century shown by hard data in Oliva et al (2019) does not preclude the existence of overgrazing and under-grazing at smaller (local) scales. Marino et al (2020) estimated that land that remains dedicated to sheep production would have 73% and 28% overgrazing in Santa Cruz and Chubut Provinces, respectively.…”
Section: Are Dome S Ti C S To Ck N Umb Er S At Equ Ilib Ri Um With supporting
confidence: 84%
“…Marino et al (2020) also mention 'ecological release (Begon, Townsend, & Harper, 2006) of guanacos after sheep removal has been documented, confirming competitive exclusion by a process-oriented approach (Burgi, Marino, Rodríguez, Pazos, & Baldi, 2012) (Table 3). Sheep and guanaco numbers were compared to the MOD17/A3 herbivore carrying capacity as presented in Oliva et al (2019;Table 3). These active farms show high densities of guanaco in interaction with sheep, and in all but one of the farms, guanaco grazing pressure in Animal Units (that compensate for mass differences between the herbivore species)…”
Section: Are Dome S Ti C S To Ck N Umb Er S At Equ Ilib Ri Um With mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, an article titled 'Remotely-sensed primary productivity shows that domestic and native herbivores combined are overgrazing Patagonia' was published in the Journal of Applied Ecology. In this article, Oliva, Paredes, Ferrante, Cepeda, and Rabinovich (2019) compared their carrying capacity (CC) estimates with wild and domestic herbivore numbers. The authors concluded that after decades of stock adjustment, total domestic grazing pressure came close to CC, but in the Chubut and Santa Cruz Provinces, guanaco Lama guanicoe populations may have altered the balance in the last two decades.…”
Section: Introductionmentioning
confidence: 99%